Effect of Ageing on Weight-Bearing Joints: Based on The Concept of Unani Medicine - Alam Ansari, Md Khursid; Rahman, Azizur; Ansari, Abid Ali; Taiyabi, Shabistan Fatma (Journal of Neonatal Surgery, 2025)
Ageing is a multi-causative meta-phenomenon that leads to progressive intrinsic deterioration of the homeodynamic capabilities of the body that challenge survival. According to the principle of Unani medicine, the cold-dry temperament of the elderly causes loss of structural integrity in organs, and a decrease in intensity of innate heat and amount of innate moisture leads to functional decline in organs over time. The structural deformity and functional decline are accomplished by gradually accumulating alien moisture. In humans, the temperament of adulthood is hot-dry (drier than the child but moister than the elderly), which is best suited for the optimal somatic and reproductive function; hence, this temperament is regarded as mu’tadil (equipoise). Whereas, the temperament of the elderly is cold-dry, which is worst for the function of life, causing structural deformity and functional decline in organs. Ageing imparts its effect on every organ, including weight-bearing joints. Joints are spacious, mobile, and weaker organs, which favor the accumulation of alien moisture. The organs that are more spacious and have greater mobility undergo earlier and severe degenerative changes due to ageing